A Novel Route to a Key Precursor in the Synthesis of (+)-Isocarbacyclin - Park, H.; Lee, Y.S.; Jung, S.H.; Shim, S.C. (1992)
A new synthetic route to a key intermediate for the synthesis of (+)-isocarbacyclin is described. ？ 1992, Taylor & Francis Group, LLC. All rights reserved.